Upaya Guru dalam Membangun Karakter Religius Melalui Program Kelas Cerdas Keagamaan - Afifah Ulya Ainurrohmah DCG; Sobar Al Ghazal (Jurnal Riset Pendidikan Agama Islam, 2024)
Abstract. This study aims to: 1) determine the objectives of the Religious Excellence Class Program, 2) understand the implementation process of the program in shaping the religious character of students, and 3) identify the supporting and hindering factors in the effort to build religious character. The findings of the study indicate that: 1) The program aims to produce graduates who are intellectually capable and have Islamic character, to train a generation of Qur’anic scholars, to develop students' self-abilities, and to enhance their confidence as Muslims. 2) The religious character being developed includes the spirit of jihad in spreading Islam, increasing religious knowledge, tolerance towards other religions, performing good deeds and avoiding wrongdoings, being a good example of ethics, love for the Quran, faith and piety, and a close relationship with Allah Swt. 3) Supporting factors for this program include school and teacher policies, the role of teachers and class supervisors, and adequate facilities and infrastructure. Meanwhile, hindering factors include a less innovative syllabus, a shortage of teachers and professional expertise, and lack of synergy between the school and parents. Abstrak. Penelitian ini bertujuan untuk: 1) mengetahui tujuan Program Kelas Cerdas Keagamaan, 2) memahami proses pelaksanaan program dalam membentuk karakter religius peserta didik, dan 3) mengidentifikasi faktor pendukung serta penghambat dalam upaya pembentukan karakter religius. Hasil penelitian menunjukkan bahwasanya: 1) Program ini bertujuan menghasilkan lulusan yang cerdas intelektual dan berwatak islami, mencetak generasi ulama Qur’ani, mengembangkan kemampuan diri peserta didik, dan meningkatkan rasa percaya diri sebagai umat Muslim. 2) Karakter religius yang dibangun meliputi semangat jihad dalam menyebarkan Islam, penambahan wawasan keagamaan, toleransi terhadap agama lain, amal ma’ruf nahi munkar, uswatun hasanah, cinta terhadap Al-Qur’an, keimanan dan ketakwaan, serta kedekatan dengan Allah Swt. 3) Faktor pendukung program ini meliputi kebijakan sekolah dan guru, peran guru dan wali kelas, serta sarana dan prasarana yang baik. Sementara faktor penghambatnya adalah silabus yang kurang inovatif, kekurangan tenaga guru dan keprofesionalan, serta ketidaksinergian antara sekolah dan orangtua.